Efeitos fíler e pozolânico do pó de vidro em argamassas - Borges, Alexandre Lopes (2021)
The activity of the cement industry results in a huge amount of CO2 emissions mainly due to the calcination of limestone. In this context, numerous researches have been approaching additions in cementitious composites to replace cement amounts in the production of mortars and concretes. It is worth noting that these additions usually come from waste from other industries, thus, in addition to reducing the amount of discarded materials, it reduces the damage caused by the inappropriate destination of this waste. However, for these replacements to be considered viable, several factors must be analyzed, seeking to know the material and its behavior given the new utility. Studies on the use of finely ground glass as a partial substitute for cement have been developed, mainly due to the verification of its good performance as a pozzolanic material with particles smaller than 300 µm. In addition to this pozzolanicity, a physical filling action by the fine grains of the material (filler effect) has been observed, which results in the improvement of the modified cementitious composite. But few studies are deepening the individual contribution of glass powder in cementitious composites due to its physical and chemical effects. Thus, this research aimed to quantify the development of mechanical properties of mortars caused by filling and the pozzolanic effect of the glass powder separately. For this, initially sought to characterize the glass powder and determine its pozzolanic activity and compare the results with those found in the literature for other additions and technical standards. Mortars were developed with different levels of volumetric replacement (0%, 10%, 20%, 30%, and 50%) of cement by finely ground glass passing through the mesh #200 (75 µm), seeking to evaluate the incorporation of glass powder in the physical and mechanical properties of mortars. To differentiate the filler effect from the pozzolanic one, limestone filler was used, whose particle size distribution is similar to the studied glass powder. Mortar characterization tests were carried out on the properties of axial compressive strength, water absorption by capillary, tensile strength by diametrical compression, and static modulus of elasticity for mortars with cement contents replaced by glass and limestone filler in the same amount. The results of the pozzolanic activity of the glass powder indicated reactivity by the Modified Chapelle and electrical conductivity tests, in addition to the chemical composition with the sum of SiO2, Al2O3, and Fe2O3 oxides greater than 70%, and amorphous predominance by XRD. The mechanical results obtained were favorable to the cement replacement content by glass powder in 20% and it was possible to verify that in all the analyzed properties there was the presence of the two effects (filler and pozzolanic) of the finely ground glass in the mortars. The slower chemical activity of the glass powder was observed in relation to cement, with 24% gain in compressive strength due to pozzolanic effect concerning the reference value at the most advanced age of the study (91 days).